ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI DAYA SAING INDONESIA DALAM MENGHADAPI MASYARAKAT EKONOMI ASEAN - Reni Juliana Sagala; Murni Daulay (Ekonomi dan Keuangan, 2015)
The purpose of this study is to determine how much the influence of Education Support, economic growth, subsidie, and exchange rate to the Competitiveness Level with the opportunities and threat of Indonesia in facing ASEAN Economic Community 2015.The data used in this reasearch is a secondary data in time series from 2001-2014. Data processing methods used by researchers is Regression Analysis by Ordinary Least Square (OLS), in with SPSS 17. Based on the results of analysis show that the independent variable is positive and has significant effect on the Competitiveness of 95.3%. Partially Education Support, Economic Growth, and exchange rate have positive effect on Competitiveness with each keofisien 0.331; 0.540; and 0.366, the variable which has the greatest effect is Economic Growth. While variable subsidies has a negatif effect on the Competitiveness with coefficient is -0.041. This will be one of the threats of Indonesia in facing AEC because it’s consumtive and missed target that foreigner will also use it. Removal and reduction of barriers to free trade as in Blueprint caused the Indonesian market dominated by imports and trade balance deficits. Indonesian Manpower become one of the opportunities and challenges for Indonesia where the skill labor that can compete with foreign labor as the criteria in "Mutual Recognition Agreement (MRA)" according to the agreement of AEC.Keywords : Asean Economic Community (AEC), Competitiveness, Blueprint, Mutual Recognition Agreement (MRA), Opportunities, Threats.